A SOCIAL WAY TO EXPERIENCE EVENTS –THE USE OF FACEBOOK AT THE CELABRATION OF THE 80THANNIVERSARY OF THE NATIONAL SPORTS ACADEMY “VASSIL LEVSKI” –SOFIA - N. Atanasova; M. Kuleva (Trakia Journal of Sciences)
The widespread use of Internet technologies has been fundamental in changing how people communicate daily and professionally. The social media revolution has completely changed internet user behavior. One of the social networks that is widely used is Facebook, which currently has more than 2 billion active users. The events with which the NSA "Vassil Levski" celebrated its 80th anniversary include the 3rd International Scientific Congress "Applied Sports Sciences", Round Table with the participation of Maria Gabriel, the gala-performance "Flight to the Stars" and more. The research aims to analyze the use of Facebook before and during these events. All Facebook posts from the NSA "Vassil Levski" were analyzed in the study in the period 29.08.2022 -20.12.2023. Based on the content analysis, data was extracted, and it was concluded that the institution's Facebook page highlights its significant role in both digital positioning and its place in building brand communication strategies.